Peripherally restricted cannabinoid 1 receptor agonist as a novel analgesic in cancer-induced bone pain. Issue 9 (September 2018) - Zhang, Hong; Lund, Dominique M.; Ciccone, Haley A.; Staatz, William D.; Ibrahim, Mohab M.; Largent-Milnes, Tally M.; Seltzman, Herbert H.; Spigelman, Igor; Vanderah, Todd W.
Abstract : Abstract: Many malignant cancers, including breast cancer, have a propensity to invade bones, leading to excruciating bone pain. Opioids are the primary analgesics used to alleviate this cancer-induced bone pain (CIBP) but are associated with numerous severe side effects, including enhanced bone degradation, which significantly impairs patients' quality of life. By contrast, agonists activating only peripheral CB1 receptors (CB1Rs) have been shown to effectively alleviate multiple chronic pain conditions with limited side effects, yet no studies have evaluated their role(s) in CIBP. Here, we demonstrate for the first time that a peripherally selective CB1R agonist can effectively suppress CIBP. Our studies using a syngeneic murine model of CIBP show that both acute and sustained administration of a peripherally restricted CB1R agonist, 4-2-[-(1E)-1[(4-propylnaphthalen-1-yl)methylidene]-1H-inden-3-yl]ethylmorpholine (PrNMI), significantly alleviated spontaneous pain behaviors in the animals. This analgesic effect by PrNMI can be reversed by a systemic administration but not spinal injection of SR141716, a selective CB1R antagonist. In addition, the cancer-induced bone loss in the animals was not exacerbated by a repeated administration of PrNMI. Furthermore, catalepsy and hypothermia, the common side effects induced by cannabinoids, were measured at the supratherapeutic doses of PrNMI tested. PrNMI induced mild sedation, yet no anxiety or a decrease in limb movements was detected. Overall, our studies demonstrate that CIBP can be effectively managed by using a peripherally restricted CB1R agonist, PrNMI, without inducing dose-limiting central side effects. Thus, targeting peripheral CB1Rs could be an alternative therapeutic strategy for the treatment of CIBP. Abstract : A novel peripherally restricted CB1R agonist effectively alleviates cancer-induced bone pain but does not exacerbate bone loss or produce dose-limiting side effects.